2007
DOI: 10.1590/s1516-93322007000100012
|View full text |Cite
|
Sign up to set email alerts
|

Validation of HPLC, DPPH• and nitrosation methods for mesalamine determination in pharmaceutical dosage forms

Abstract: Mesalamine (5-aminosalicylic acid, 5-ASA) is used because of its local effects in the treatment

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 13 publications
(21 reference statements)
0
9
0
Order By: Relevance
“…Determination of mesalamine related impurities by micellar electrokinetic chromatography with an ion-pair reagent was reported 33 . Mesalamine determination in pharmaceutical dosage forms by HPLC, DPPH and nitrosation was also reported 34 .…”
Section: Introductionmentioning
confidence: 99%
“…Determination of mesalamine related impurities by micellar electrokinetic chromatography with an ion-pair reagent was reported 33 . Mesalamine determination in pharmaceutical dosage forms by HPLC, DPPH and nitrosation was also reported 34 .…”
Section: Introductionmentioning
confidence: 99%
“…Few visible spectrophotometric methods are found in the literature for the assay of MSL. In a method reported by Rafael et al, 10 hydrogen donating ability of MSL to 1, 1-diphenyl-2-picrylhydrazyl radicals is used as basis for its determination in pharmaceutical dosage forms. Patel et al, 27 reported three methods for the assay of MSL in tablet dosage forms with Bratton-Marshall reagent, p-dimethylaminobenzaldehyde and Gibb's reagent.…”
Section: Introductionmentioning
confidence: 99%
“…Different methods have been reported for the determination of mesalazine. These methods include: Amicellar electrokinetic chromatography with ion-pair reagent [3], high performance liquid chromatography (HPLC) methods [4][5][6], voltametry [7] and fluorometry [8]. Several spectrophotometric methods have been used for the determination of mesalazine, such as UV method [1], charge transfer complex [9], diazotization of mesalazine and coupling with N-(1naphyl) ethylene diamine [10] or resorcinol [11].…”
Section: Introductionmentioning
confidence: 99%